Acquisition plan for a merchant practicing duple admissible lag in payment. (2022) - Shaikh, Azharuddin; Mishra, Poonam; Talati, Isha
Abstract: This work anticipates an optimal inventory acquisition plan for a merchant. The phenomenon of allowable time period for account settlement is inculcated to have practical impression. The merchant acquires an interest free time to disburse procuring price and lends time to clients which can intensify the demand. In addition, merchant has two different time periods to choose from for paying the sum, either to pay a discounted price in the first span or that with no discount in the second. The motive is to determine number of acquiring units and to figure out suitable alternative for the merchant to pay. The situation is mathematically modelled and a solution procedure is devised to determine optimal solution. Lastly, impact of each parameter is examined and insights are conferred.